Fault Diagnosis and Tolerance for Open-circuit Faults in Multi-Level Inverters - Halabi, Laith M.; Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (2022 International Power Electronics Conference, IPEC-Himeji 2022-ECCE Asia, 2022)
This paper presents a creative method for detecting and tolerating open circuit faults in a three-level hybrid active neutral point clamped (HANPC) converter. The faults have direct effects on the output voltages and currents of the three-phase system. Therefore, the early detection and tolerance would enhance the system's reliability and stability. The detection method mainly depends on calculating the current distortion that is resulting from the fault effects on the system. Meanwhile, the fault tolerance depends on creating new voltage references and inserting new switching sequences under faulty conditions. As a result, the system is capable to identify the fault location and recover the healthy (normal) performance under the faulty conditions. The proposed method is verified in the simulation results.
Keywords: Active neutral point clamped; Active neutral point clamped inverter; Creatives; Fault diagnosis and tolerances; Faults detection; Faulty condition; Multi-level inverter; Multilevels; Neutral-point clamped inverters; Open-circuit fault; Active neutral point clamped inverters; Fault detection; Multi-level inverters; Open circuit faults